1995
DOI: 10.1063/1.469889
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the Compton profile of C60 through binary encounter electron spectroscopy

Abstract: The method of 0° electron spectroscopy was used to study binary encounter electrons resulting from hard collisions between 1.5 MeV/u C6+ ions and the electrons in a C60 vapor target. The Compton profile of C60 was then extracted from the electron spectra using an impulse approximation treatment. The experimental results are in excellent agreement with theoretical Compton profiles of C60. The C60 Compton profile is compared with that of atomic carbon, as well as those for graphite and diamond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Additional data which concern the correlation between the ionization or fragmentation of the molecule and low energy electrons (not well-defined energies, see below) will illustrate some properties of the capture reaction. Electron spectroscopy in a similar system, C 6+ -C 60 , was reported a few years ago by other authors [14], but at much higher collision velocity (1.5 MeV/amu) where the collisional processes are very different from the ones discussed here.…”
supporting
confidence: 70%
“…Additional data which concern the correlation between the ionization or fragmentation of the molecule and low energy electrons (not well-defined energies, see below) will illustrate some properties of the capture reaction. Electron spectroscopy in a similar system, C 6+ -C 60 , was reported a few years ago by other authors [14], but at much higher collision velocity (1.5 MeV/amu) where the collisional processes are very different from the ones discussed here.…”
supporting
confidence: 70%
“…It was suggested that the GDPR has a profound influence on the energy loss of the projectile. However, most of these studies were focused on measuring the GDPR contribution on the recoil-ion yields, whereas the electronspectroscopy-based measurements using a free C 60 molecule as the target are rather limited [9,[34][35][36][37]. This lack of experimental investigations on electron spectroscopy of C 60 can be, in part, attributed to the difficulties in detecting low-energy electrons.…”
Section: Introductionmentioning
confidence: 96%
“…Though the relative difference is rather small, the experiment clearly favours the C 60 calculation. We mention that recent Compton profile data obtained from the measurement of the binary-encounter electron peak in 18 MeV C 6+ /C 60 collisions [36] did not reveal any difference between a C 60 and a graphite Compton profile. We emphasize that the comparison of figure 7 and figure 6 relies on the fact that the graphite target, in particular, had spherically distributed crystallites.…”
Section: Resultsmentioning
confidence: 67%